A nationwide survey of healthcare personnel’s attitude, knowledge, and interest toward renal supportive care in Taiwan - Tsai, Hung-Bin; Chao, Chia-Ter; Huang, Jenq-Wen; Chang, Ray-E; Hung, Kuan-Yu; COhort of GEriatric Nephrology in NTUH (COGENT) study group (PeerJ, 2017)
Background Renal supportive care (RSC) is an important option for elderly individuals reaching end-stage renal disease; however, the frequency of RSC practice is very low among Asian countries. We evaluated the attitude, the knowledge, and the preference for specific topics concerning RSC among participants who worked in different medical professions in Taiwan. Methods A cross-sectional questionnaire-based survey was employed. Healthcare personnel (N = 598) who were involved in caring for end-stage renal disease patients at more than 40 facilities in Taiwan participated in this study. Participants were asked about their motivation for learning about RSC, the topics of RSC they were most and least interested in, their willingness to provide RSC, and to rate their knowledge and perceived importance of different topics. Results The vast majority of respondents (81.9%) were self-motivated about RSC, among whom nephrologists (96.8%) and care facilitators (administrators/volunteers) (45%) exhibited the highest and the least motivation, respectively (p < 0.01). Overall, respondents indicated that they had adequate knowledge about the five pre-specified RSC topics between medical professions (p = 0.04). Medical professions and institutional size exerted significant influence on the willingness to provide RSC. Conclusions Our results facilitate the understanding of the knowledge and attitude toward different RSC topics among varied medical professions, and can guide the design of RSC education content for healthcare personnel.
Keywords: End-stage renal disease; Dialysis; Medical center; Renal supportive care; Taiwan; Cross-sectional studies; Palliative care; Allied health occupations; Medical education